2021
DOI: 10.1097/md.0000000000025871
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of end-stage lymphedema following radiotherapy for lymphoma

Abstract: Rationale : Despite significant advances in microsurgical techniques, simultaneous vascularized lymph node transfer (VLNT) and lymphovenous anastomosis (LVA) surgeries may be effective for treatment of end-stage lymphedema. This case report describes the successful treatment of end-stage lymphedema with VLNT and LVA. Patient Concerns: A 72-year-old patient with bilateral lower extremity lymphedema was referred to our lymphedema clinic. This patient had a history of lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Agko et al, 45 in a prospective study for patients with advanced-stage II lymphedema, showed that a staged surgical approach involving VLNT followed by suction-assisted lipectomy resulted in a significant reduction in limb size, nearly restoring it to normal levels, and effectively eliminated instances of infections. In our systematic review and meta-analysis, most of included studies reporting lymphedema stage included advanced stages such as stage II and III, this is with alignment that VLNT alone can demonstrate satisfactory enhancement in individuals with advanced-stage lymphedema, while LVA is thought of in early stage, such as stage I lymphedema 46 …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, Agko et al, 45 in a prospective study for patients with advanced-stage II lymphedema, showed that a staged surgical approach involving VLNT followed by suction-assisted lipectomy resulted in a significant reduction in limb size, nearly restoring it to normal levels, and effectively eliminated instances of infections. In our systematic review and meta-analysis, most of included studies reporting lymphedema stage included advanced stages such as stage II and III, this is with alignment that VLNT alone can demonstrate satisfactory enhancement in individuals with advanced-stage lymphedema, while LVA is thought of in early stage, such as stage I lymphedema 46 …”
Section: Discussionmentioning
confidence: 62%
“…In our systematic review and meta-analysis, most of included studies reporting lymphedema stage included advanced stages such as stage II and III, this is with alignment that VLNT alone can demonstrate satisfactory enhancement in individuals with advancedstage lymphedema, while LVA is thought of in early stage, such as stage I lymphedema. 46 Limitations and Future Prospective…”
Section: Limb Circumference Reduction Rate and Postoperative Infectio...mentioning
confidence: 99%